Possible Impact of the Construction of the Belo Monte Hydroelectric Power Plant on Cases of Congenital Syphilis in the Xingu Region (Global Journal of Medical Research, 2023)
Syphilis is considered a serious public health problem in Brazil and worldwide The disease is especially worrying during pregnancy as the mother can transmit the infection to her fetus causing congenital syphilis In this context few articles have established a causal relationship between the growth in the number of cases of gestational and congenital syphilis in the Xingu Region and the construction of the Belo Monte Hydroelectric Plant Objective This study aims to analyze the influence of the intense migratory flow resulting from the construction of the Belo Monte Hydroelectric Power Plant on the cases of congenital syphilis
Keywords: pregnancy complications; infectious; syphilis; congenital syphilis; epidemiology; analytical epidemiology